2022
DOI: 10.1002/jcla.24424
|View full text |Cite
|
Sign up to set email alerts
|

LINC00240 knockdown inhibits nasopharyngeal carcinoma progress by targeting miR‐26a‐5p

Abstract: Objective: This study intended to explore the regulatory functions of LINC00240 on nasopharyngeal carcinoma (NPC).Methods: MiR-26a-5p inhibitor, mimic, and siLINC00240 were transfected into NPC cells. QRT-PCR was employed to assess miR-26a-5p and LINC00240 expressions.The targeting relationship of LINC00240 and miR-26a-5p was analyzed through dual luciferase reporter and RNA immunoprecipitation assay. Cell counting kit-8 assay, colony formation assay, flow cytometry assay, wound healing assay, Transwell assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Nasopharyngeal carcinoma (NPC), which originates from nasopharyngeal epithelial cells, 1,2 is one of the most common types of head and neck cancer in parts of Southeast Asia, Southern China, and North Africa, with 5‐year survival rates of 70%–80% 3,4 . Distant metastasis and local and regional recurrences that affect the long‐term survival of patients are the primary reasons for treatment failure 5 . According to statistics, local recurrence occurs in 5%–10% of patients and distant metastasis occurs in 10%–20% of patients after treatment 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC), which originates from nasopharyngeal epithelial cells, 1,2 is one of the most common types of head and neck cancer in parts of Southeast Asia, Southern China, and North Africa, with 5‐year survival rates of 70%–80% 3,4 . Distant metastasis and local and regional recurrences that affect the long‐term survival of patients are the primary reasons for treatment failure 5 . According to statistics, local recurrence occurs in 5%–10% of patients and distant metastasis occurs in 10%–20% of patients after treatment 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent microarray analyses have discovered a number of dysregulated lncRNAs in AR which might be associated with allergic inflammation [12,30,31], however, the mechanisms by which these altered lncRNAs contribute to AR pathogenesis merit in-depth investigation. Several studies have illustrated the critical roles of LINC00240 in cancer biology, and identified related ceRNA networks in different cancers [13][14][15][16][17]. For instance, silencing of LINC00240 suppresses cell growth, metastasis and angiogenesis via miR-26a-5p in NPC [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have illustrated the critical roles of LINC00240 in cancer biology, and identified related ceRNA networks in different cancers [13][14][15][16][17]. For instance, silencing of LINC00240 suppresses cell growth, metastasis and angiogenesis via miR-26a-5p in NPC [17]. Our preliminary bioinformatics analysis showed reduced expression of LINC00240 in AR patients, and this data was verified by qRT-PCR in the peripheral blood and nasal mucosa of AR patients, as well as in the nasal mucosa of AR mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-1297 and miR-26a-5p are other miRNAs that have been studied in cholesteatoma and are widely investigated in oncology. The inhibitory effect of miR-1297 on cancer progression has been observed in various malignant entities [113][114][115][116][117][118][119][120][121][122][123][124]. In addition to its role in tumorigenesis, miR-26a-5p similarly plays an important role in pulmonary fibrosis [125] and Alzheimer's disease [126].…”
Section: Microrna-802mentioning
confidence: 99%